Farewell Words: In Memory of Alexander I. Dontsov - Inna B. Bovina (Peoples' Friendship University of Russia (RUDN University), 2023)
The article is dedicated to the memory of Professor Alexander I. Dontsov (1949-2023), Doctor of Psychology, Professor of the Social Psychology Department at Lomonosov Moscow State University, Emeritus Professor of Lomonosov Moscow University, Academician of the Russian Academy of Education. The author shares her memories of the interaction with A.I. Dontsov during his studies and work at the Department of Social Psychology, Faculty of Psychology, Lomonosov Moscow State University.